TOWARDS AGE-FRIENDLY CITIES: METHODOLOGICAL, PRACTICAL AND THEORETICAL INSIGHTS FROM CROSS-NATIONAL RESEARCH. (11th November 2018) - Woolrych, R
Abstract: Ageing populations have raised specific opportunities and challenges in terms of how we can design urban environments to support older adults to age-in-place. Urban areas can bring benefits in old age, in terms of access to service and amenities, cultural supports and necessities for daily living. At the same time, urban environments can create feelings of insecurity, loneliness and isolation which may enhance vulnerability and undermine active ageing. Ageing in urban environments has received significant policy attention and guidance regarding the provision of accessible outdoor spaces and buildings, alongside opportunities for civic and social participation. Whilst these policy drivers demonstrate progress, there has been a paucity of case study research exploring experiences of ageing across urban, social and cultural contexts. As a result, there has been a tendency to generalise findings across communities, assuming a one-size fits all approach, which may fail to capture the nuances of ageing across international contexts. The objective of this symposium is to reflect on research undertaken across 6 cities and 18 neighbourhoods in the UK and Brazil as part of a 3 year ESRC project Place Making with Older Adults: Towards Age-friendly Communities. Through three inter-linked papers we will explore: 1. Understandings of ageing as experienced by older adults across different urban and cultural contexts; 2. The application of visual and creative methods and their power in understanding the place-based needs of older adults; and 3. Potential ways forward for how ageing across trans-national contexts can inform the development of age-friendly cities and communities.